A conceptual framework of transformational and transactional leadership on nurse educators job satisfaction - Moey, Soo Foon (Research Publish Journals, 2016)
The conceptual framework is based on the Full Range Leadership by Avolio and Bass (2004) that theorized that transformational leadership can be clustered in five sub-constructs whilst the transactional leadership into two sub-constructs. Each dimension is measured using four items. The Full Range Leadership Theory being an effective leadership theory uses both transformational and transactional attributes in differing degrees depending on the situation and the ability of the subordinates. Even though transactional leadership is not able to develop trust and full potential of the followers but if coupled with the individualized consideration attribute of the leader, it can provide the platform for transformational leadership to ensue. This then can positively affect subordinates’ motivation and performance. Organizations presently are marked by high interdependency and integration; hence the need for leadership that goes beyond that of transactional to transformational leadership styles with attributes such as inspiration, stimulation, motivation and charisma as these attributes are believed to be able to bring about cohesion, commitment, trust and performance. The conceptual framework assumes that transformational and transactional leadership-work place engagement is indirect and impacted through the mechanism of perceived subordinates’ well-being, ultimately leading to job satisfaction. The importance of the nursing administrator in determining the nature of work environment is well documented and is of increasing significance to the retention of nurse educators. Perception of work place engagement could play the role of perceived work environment and thus mediate between the relationship between leadership styles and job satisfaction of subordinates.